2013
DOI: 10.18438/b80g6v
|View full text |Cite
|
Sign up to set email alerts
|

Coding Practices for LibQUAL+® Open-Ended Comments

Abstract: 2013 Neurohr, Ackermann, O'Mahony, and White. This is an Open Access article distributed under the terms of the Creative Commons-Attribution-Noncommercial-Share Alike License 2.5 Canada (http://creativecommons.org/licenses/by-nc-sa/2.5/ca/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. Abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The third category discusses practical approaches of using LibQUAL surveys for qualitative and quantitative analysis (such as Voorbij, 2012;Neurohr, Ackermann, O'mahony, & White, 2013;Killick, Weerden, & Weerden, 2014;Deltor & Ball, 2015). Thompson, Cook, & Health, 2001;Hossain, 2016;Boyce, 2017) during the process of the LibQUAL assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The third category discusses practical approaches of using LibQUAL surveys for qualitative and quantitative analysis (such as Voorbij, 2012;Neurohr, Ackermann, O'mahony, & White, 2013;Killick, Weerden, & Weerden, 2014;Deltor & Ball, 2015). Thompson, Cook, & Health, 2001;Hossain, 2016;Boyce, 2017) during the process of the LibQUAL assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of all, 55.8 per cent of respondents reported only one coder and an additional 26.9 per cent reported two coders. Time was the single largest challenge experienced by participants, followed by difficulties with the process of coding, insufficient technology and insufficient staff (Neurohr et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, respondents reported that they were analyzing LibQUALϩ comments to make improvements within the library and to communicate with administrative and non-administrative university stakeholders. Only 25.5 per cent of respondents listed publication and conference presentation as among their uses of the data (Neurohr et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the teams considered a variety of software packages for coding, such as Atlas.ti or NVivo, due to cost restrictions (project funding did not cover the purchase of software for all team members tasked with coding), the time necessary to train team members in these software packages, and computer hardware considerations (eight individuals on the Columbia team were using five different computer operating systems), the team chose a coding approach using Microsoft Word, developed at the Brown University Library (Neurohr, Ackermann, O'Mahony, & White, 2011).…”
Section: Codingmentioning
confidence: 99%